2006
DOI: 10.1158/1535-7163.mct-05-0456
|View full text |Cite
|
Sign up to set email alerts
|

A novel norindenoisoquinoline structure reveals a common interfacial inhibitor paradigm for ternary trapping of the topoisomerase I-DNA covalent complex

Abstract: We show that five topoisomerase I inhibitors (two indenoisoquinolines, two camptothecins, and one indolocarbazole) each intercalate between the base pairs flanking the cleavage site generated during the topoisomerase I catalytic cycle and are further stabilized by a network of hydrogen bonds with topoisomerase I. The interfacial inhibition paradigm described for topoisomerase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 61 publications
1
133
0
Order By: Relevance
“…1A). Based on the crystal structure, there exists a structural overlap between CPT and the indenoisoquinolines in their interaction with Top1-DNA complexes (14)(15)(16). Structural similarity could account for the trapping of DNA-Top1 cleavage complexes at similar sites between CPT and the indenoisoquinolines NSC 725776, NSC 724998, and NSC 706744 (sites 70, 92, 97, and 119; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Based on the crystal structure, there exists a structural overlap between CPT and the indenoisoquinolines in their interaction with Top1-DNA complexes (14)(15)(16). Structural similarity could account for the trapping of DNA-Top1 cleavage complexes at similar sites between CPT and the indenoisoquinolines NSC 725776, NSC 724998, and NSC 706744 (sites 70, 92, 97, and 119; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We have now synthesized and tested >300 indenoisoquinoline derivatives and found that some of them are both very potent Top1 poisons and exhibit antitumor activity in mouse models (10)(11)(12)(13). We have also obtained crystal structures of two different indenoisoquinolines within Top1 cleavage complexes (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Threedimensional structure analyses of a ternary complex formed between Top1, DNA, and CPT or topotecan by X-ray crystallography (6,11) showed that one drug molecule interacts both with the DNA base pairs flanking the cleavage sites and three key amino acid residues of Top1 (Asn 722 , Arg 364 , and Asp 533 ; ref. 12). Single mutation of any of those three amino acid residues is sufficient to confer high resistance to CPT and its analogues (13).…”
Section: Introductionmentioning
confidence: 99%
“…The E-ring of CPT (Fig. 1A) is essential to the interaction of the drug with the Top1-DNA cleavage complex (6,11,12). Because CPT analogues are the only clinical drugs targeting Top1, and because of their clinical importance, the search for novel inhibitors of Top1 is ongoing (2).…”
Section: Introductionmentioning
confidence: 99%
“…Under physiological conditions (pH 7.2-7.4) the carboxylate form predominates. However only the lactone form of these compounds is responsible for their biological activity to interact with the topoisomerase-I and DNA complex (Hertzberg et al, 1989;Capranico et al, 2007;Marchand et al, 2006). The structures of topotecan and irinotecan and pH-dependent conversions are shown in Figure 1-1. …”
Section: Camptothecin Analogsmentioning
confidence: 99%